Antioxidant enzyme activities and lipid peroxidation in patients with bipolar affective disorder - Dubey, Raju Kumar; Gautam, Narayan; Dhakal, Niraj; Baral, Nirmal; Lamsal, Madhab; Shyangwa, Pramod M. (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Brain is particularly vulnerable to oxidative free radicals. Oxidative stress might primarily or secondarily be involved in the pathogenesis of Bipolar Affective Disorder. Therefore this study was aimed to estimate & compare parameters of oxidative stress and antioxidant levels in patients with Bipolar Affective Disorder and healthy controls. MATERIAL AND METHODS: A total of 32 Bipolar Affective Disorder patients and 30 healthy subjects were recruited in this study. Plasma MDA level was measured as indicator of lipid peroxidation and SOD and CAT activities were determined as a measure of antioxidant status. RESULT: Out of total Bipolar Affective Disorder patients 21 were in mania with psychotic symptoms, 8 were in mania without psychotic symptoms and only 3 were in mixed episode. Significantly (p<0.001) elevated MDA level (nmol/ml) was found in before treatment patient group (7.11 ± 1.62) as compared to control (3.02 ± 1.30) group. Patients on follow-up also had significantly increased MDA level (nmol/ml) (5.37 ± 1.36) as compared to control group and decrease in level was significant (p<0.001) in comparison to before treatment patients. CAT and SOD activities (U/gm Hb) were significantly decreased in both before treatment (87.57 ± 28.79 & 1341 ± 167.18) and after treatment (77.12 ± 29.48 & 1305.56 ± 154.86) patients group compared to the control (155.92 ± 29.43 & 1408.14 ± 78.82) group respectively. CAT and MDA were negatively correlated in the before treatment patients group (r = -0.356, p<0.05). CONCLUSION: The findings suggest that there is increased oxidative stress in Bipolar Affective Disorder patients in comparison to controls.